2012
DOI: 10.2214/ajr.11.7568
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Radiofrequency Ablation of Hepatocellular Carcinoma: Fusion Imaging Guidance for Management of Lesions With Poor Conspicuity at Conventional Sonography

Abstract: Fusion imaging-guided percutaneous RFA is effective in the management of HCC that has poor ultrasound conspicuity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
94
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(97 citation statements)
references
References 25 publications
3
94
0
Order By: Relevance
“…Both the transmitter and sensors are connected to a fully integrated position sensor unit embedded in the ultrasound machine. 2 The first image fusion step was to upload the CT or MRI data to the ultrasound machine. First, the radiologist who performed the liver biopsy reviewed the CT or MR images and decided which image would be better for image fusion.…”
Section: Fusion Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Both the transmitter and sensors are connected to a fully integrated position sensor unit embedded in the ultrasound machine. 2 The first image fusion step was to upload the CT or MRI data to the ultrasound machine. First, the radiologist who performed the liver biopsy reviewed the CT or MR images and decided which image would be better for image fusion.…”
Section: Fusion Imagingmentioning
confidence: 99%
“…[1][2][3][4] Fusion imaging can facilitate accurate localization of the target lesion and eventually allow lesions to be targeted with a higher degree of confidence during interventional procedures. 2,3,5,6 Although previous studies of fusion imagingguided biopsy showed promising results, they had vague inclusion criteria and lacked homogeneity of the patient population. 7,8 Hence, a well-organized study focusing on the advantages of fusion imaging-guided percutaneous liver biopsy is still required.…”
mentioning
confidence: 99%
“…Previous studies [21][22][23] reported that ultrasound-CECT/CEMRI image fusion technique could detect more tumours than conventional ultrasound (53.3-98% vs 38.8-66%), and it facilitates RFA for liver tumours with poor conspicuity on conventional ultrasound. 17,[24][25][26] However, even with the help of ultrasound-CECT/CEMRI fusion, some lesions still show suboptimal conspicuity on the images of conventional ultrasound, and CEUS is often necessary to confirm the exact location and configuration of the target lesion. The fusion of CEUS and CECT/CEMRI before RFA might further enhance the lesion conspicuity and operator confidence in that the inconspicuous lesions would show arterial hyperenhancement in both modalities, thus the lesions are easily detectable.…”
Section: Introductionmentioning
confidence: 99%
“…80 Two cohort studies showed an excellent technical success rate, safety and effectiveness for RFA using fusion imaging. 81,82 Reduced energy diffusion is a complication observed in RFA using conventional electrodes. Utilizing internally cold (IC) electrodes and saline-enhanced RFA are two techniques to overcome this drawback.…”
Section: Rfamentioning
confidence: 99%